A novel cochlear implant assessment tool: Audiometric and speech recognition analysis - Fernanda Ferreira Caldas; Byaka Cagnacci Buzo; Bruno Sanches Masiero; Alice Andrade Takeuti; Carolina Costa Cardoso; Fabiane de Castro Vaz; Fayez Bahmad, Jr. (Brazilian Journal of Otorhinolaryngology)
Objective: To compare the results of Pure Tone Audiometry (PTA) and speech recognition, of users of Cochlear Implant (CI) between CLABOX with Direct Audio Input (DAI) and the Sound Booth (SB). Methods: Fifty individuals with CIs, 33 adults and 17 children, were included. Speech recognition tests in noise fixed and adaptive were applied with the Hearing in Noise Test (HINT), Ling test, and PTA, in the SB (in free field) and in CLABOX. Results: For speech recognition in noise, averages were better in the CLABOX; for PTA, they were higher in the CLABOX; and for Ling test, there was no significant change in the categories between SB and CLABOX. The fixed noise were higher in the CLABOX (88.3%) than in the SB (78.9%), p-value < 0.001. In the HINT with adaptive noise, the results were significant (p-value = 0.007); the S/N ratio was 2.14 dB in the CLABOX and 3.42 dB in the SB. For the four-tone average, the average thresholds for the CLABOX and the SB were 29.8 dB and 23 dB, respectively (p-values < 0.001). Conclusion: CLABOX was an effective tool to evaluate the PTA and speech recognition tests when compared to the conventional evaluation with a SB in the CI user population.